The impact of Malaysian Cocoa Board (MCB) promotional tools: Advertising, direct marketing and public relation in fostering public awareness towards cocoa consumption / Dk Ashykin Pg Omar Ali Shaiffuddin - Pg Omar Ali Shaiffuddin, Dk Ashykin (2013)
This paper encompassed the topic of strategies that produced by Malaysia Cocoa Board in order to give impact to public awareness .The purpose of the study are to identify the promotional activities done by Malaysian Cocoa Board, to determine the effectiveness of promotional activities toward public awareness and to identify the promotional activities succeed in creating consumer awareness. In doing this research, the researcher look aspects in promotional tools (advertising and publicity, direct marketing, public relation and etc.).This aspect had been set to put in the questionnaire and it will help researcher to gather information in order to achieve the objectives.